The Development of Musicalization Poetry assisted by Artificial Intelligence - Helmanto, Fachri; Dayana, Yuliana Fatima (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
The major objective of this work is to investigate the evolution of musicalization poetry with the assistance of deep artificial intelligence (AI). Educational context learning at the school level. This research utilised 4D model research and development (R&D) methodologies, encompassing the stages of Define, Design, Develop, and Disseminate. During the Define stage, an article analysis is conducted to define the theme of poetry. The Design step entails students creating poetry that aligns with predetermined themes. Artificial intelligence (AI) tools like ChatGPT and Suno Music Generator are employed at the Develop stage to transform poetry into music. The dissemination phase included conducting experiments at 20 schools in Sukabumi, where students were selected as samples to receive bait and return. Research findings indicated that the usage of AI apps can significantly enhance language competency, creativity, and cultural understanding among students. Evidence-based 4D research and development approach successful in combining poetry with musicalization. Nevertheless, issues such as linguistic complexity and instructor competence have to be addressed. In general, the use of artificial intelligence in musicalising poetry represents significant promise. In order to enhance the learning experience and increase student engagement in literary education.